Applying Microsoft Forms Software in Formative Assessment in Teaching Mathematical Concepts for 7th Graders in Vietnam (Journal of Contemporary Educational Policies and Practices, 2024)
Formative assessment, a cornerstone of competency-based teaching, plays a pivotal role in enhancing learner progress. In Vietnamese schools, its potential for driving educational transformation is ripe for exploration. This research delves into the innovative use of Microsoft Forms as a digital tool for designing formative assessment tools for 7th-grade mathematics, with a focus on key mathematical concepts in the curriculum. The study adopts a robust mixed-method approach, combining qualitative and quantitative analyses. It engaged 116 7th-grade students from secondary schools in Quang Ninh, Phu Tho, Nam Dinh, and Thai Binh provinces. Additionally, semi-structured interviews were conducted with 30 mathematics teachers from the same regions, providing deep insights into the practical application of this technology. The findings highlight the significant impact of Microsoft Forms in fostering effective formative assessment. Teachers can anticipate student difficulties, identify common errors, and respond with timely, tailored interventions. Students, in turn, show heightened interest and confidence in the classroom, embracing mathematical concepts with enthusiasm. The research also introduces two innovative techniques to enhance the skills of both teachers and students in leveraging Microsoft Forms effectively. This study underscores the transformative potential of digital tools in modern education, particularly within the framework of Vietnam’s 2018 General Education Curriculum for mathematics. It concludes by recommending the broader adoption of Microsoft Forms across diverse teaching scenarios, signaling a new era in math education where technology bridges gaps and unlocks student potential.
Keywords: Formative assessment; Microsoft Forms software; mathematical concepts; grade 7